Sediment echosounder raw data (Innomar SES-2000 entire dataset) of RV ALKOR during cruise AL575 - Mia Schumacher; Matthias Haeckel; Mark Schmidt (PANGAEA, 2025)
Raw sub-bottom data were collected aboard RV ALKOR during cruise AL575 using a SES2000 parametric subbottom profiler system by Innomar, operating at a combination of three frequencies, 5, 10 and 15 kHz. It may penetrate the seafloor down to around 40m, depending on substrate and amongst others reveal submerged gas cavities that can potentially rise and enter the water column as bubble streams. The Seswin v 1.7.7. acquisition software was used to record .raw & .ses data with following settings: Low Frequency 6-8 kHz (depending on depth) Low Frequency Pulse length 1-2/s Depth Range Water depth + 12m Gain Low F: 15dB, High F: 4dB The expedition took place during 2022-06-28 – 2022-07-13 from Kiel to Kiel (Germany) in the North Sea. The major aim of AL575 - GEOSTOR leak are to investigate and contribute to the assessment of the mechanisms and potential risks of CO2 leakage along boreholes drilled through the sedimentary overburden above subseafloor storage formations in the North Sea. Data were recorded in the EEZs of UK and Germany. Please see the cruise report for details. The data are unprocessed and can therefore contain incorrect measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition and provision was done by GEOMAR and they are published according to the FAIR principles.